Electrophoretic deposition of lawsone loaded bioactive glass (BG)/chitosan composite on polyetheretherketone (PEEK)/BG layers as antibacterial and bioactive coating. Issue 12 (14th September 2018) - Ur Rehman, Muhammad Atiq; Bastan, Fatih Erdem; Nawaz, Qaisar; Goldmann, Wolfgang H.; Maqbool, Muhammad; Virtanen, Sannakaisa; Boccaccini, Aldo R.
Abstract: In this study, chitosan/bioactive glass (BG)/lawsone coatings were deposited by electrophoretic deposition (EPD) on polyetheretherketone (PEEK)/BG layers (previously deposited by EPD on 316‐L stainless steel) to produce bioactive and antibacterial coatings. First, the EPD of chitosan/BG/lawsone was optimized on stainless steel in terms of suspension stability, homogeneity and thickness of coatings. Subsequently, the optimized EPD parameters were used to produce bioresorbable chitosan/bioactive glass (BG)/lawsone coatings on PEEK/BG layers. The produced layered coatings were characterized in terms of composition, microstructure, corrosion resistance, in vitro bioactivity, drug release kinetics and antibacterial activity. Ultraviolet/Visible (UV/VIS) spectroscopic analyses confirmed the release of lawsone from the coatings. Moreover, the deposition of chitosan/BG coatings was confirmed by Scanning Electron Microscopy (SEM) and Fourier Transform Infrared spectroscopy (FTIR). The coated specimens presented higher corrosion resistance (10 times) in comparison to that of bare 316‐L stainless steel and showed convenient wettability for initial protein attachment. The presence of lawsone in the top layer provided antibacterial effects against Staphylococcus carnosus. Moreover, the developed coatings formed apatite‐like crystals upon immersion in simulated body fluid, indicating the possibility of achieving close interaction between the coating surface and bone. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 3111–3122, 2018.